Synthesis of 2-Thiophenyl-3-substituted Phenyl-4-oxo Thiazolidine - Idrees Mohd. Siddique, Mohd.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
4-Thiazolidinones have been reported to possess biological activity. 2-Thiophenylidine substituted aniline, condensed with thioglycolic acid in benzene medium, gives 2-thiophenyl-3-substituted phenyl-4-oxo-thiazolidine. The structure of 2-thiophenyl-3-substituted phenyl-4-oxo-thiazolidine were confirmed by spectral and chemical data.